BUDGETARY POLICY OF THE RUSSIAN FEDERATION IN CONDITIONS OF ECONOMIC UNCERTAINTY - O. A. Polyakova; R. A. Alandarov (Финансы: теория и практика, 2017)
In crisis conditions the role of fi scal policy of any state increases because, as a rule, it is the sphere of state and municipal fi nances that provides a resource which enables to give an impetus to the economic revival. At present, this area is particularly important for the Russian Federation as the domestic economy has faced numerous internal and external challenges. Such factors as the decline in production, increased speculation on the foreign exchange market, the weakening of the ruble which has led to higher prices for imports, sanctions against a number of Russian companies and banks make the state more actively intervene in economic processes and strengthen state regulation of the economy. Current rules of budgetary and tax legislation contain some shortcomings which are especially conspicuous in the period of stagnation. Mid-term measures scheduled in the budgetary area before the crisis should be updated. In this connection, it is particularly important to analyze the main trends in the approaches to the management in budgetary sphere. The world experience has shown that one of the most important and diffi cult problems facing public authorities in times of crisis is the need to optimize government spending: to cancel or to postpone spending aimed at minor results. On the other hand, a large part of budgetary expenses is associated with the government’s constitutional responsibilities towards its citizens. In this regard, it is important to analyze the measures formulated by the Russian government in its anti-crisis budgetary policy. The article describes the preconditions for carrying out anti-crisis measures in the budgetary policy area as well as implementation tools. The authors put forward proposals for amendments to be introduced in the current budgetary legislation of the Russian Federation as well as the necessary adjustments of the budget strategy.